Disain Dan Simulasi Generator Magnet Permanen 3 Phasa Menggunakan Softwawre Magnet Untuk Pembangkit Listrik Tenaga Angin Kecepatan Rendah - Irfan, Joni; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia is a country that has abundant energy resources and is built on the trajectory of the equator, so it has the potential to be used as a Wind Power Plant. The permanent magnet synchronous generator (GSMP) is the main component of the wind power generation. The author designs the GSMP using the MagNet Infolityca software. In designing the author publishes a number of journal guidelines and design specifications of products that synchronize permanent magnet generators marketed in the market. In accordance with technological developments and market requirements, in the study the authors agreed to the GSMP with the specifications of 18 12-pole slots with inter-phase voltage output of 41.5 volts AC, and 500 watts of power. This GSMP has a winding factor of 0866, because it uses the single layer lap winding winding method. The inter phase output voltage from the generator simulation is 39.88 V AC, with the effective voltage value is 56.40 V AC. When compared with the calculation obtained the difference (error) of 1.62% for the value of voltage between phase and 1.65% for effective voltage.Keywords: 3 phase Permanent Magnet Synchronous Generator, MagNet Infolytica, Wind power generator, low speed.